The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fmolb.2022.831293
|View full text |Cite
|
Sign up to set email alerts
|

A Species-Specific Strategy for the Identification of Hemocoagulase Agkistrodon halys pallas Based on LC-MS/MS-MRM

Abstract: Hemocoagulase Agkistrodon halys pallas is a complex mixture composed of snake venom thrombin-like enzymes (svTLEs) and small amounts of thrombokinase-like enzymes. It has been widely used as a hemostatic with rapidly growing marketing due to its advantage of localized clotting fibrinogen other than systemic coagulation. However, svTLEs from different species have various structures, functions, and hemostatic mechanisms. To ensure the efficacy and safety of Hemocoagulase Agkistrodon halys pallas, an exclusive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Previous studies [19,20] have demonstrated that the application of hemocoagulase during hepatobiliary surgery can effectively reduce intraoperative bleeding volume without affecting the coagulation functions of patients. Furthermore, other studies [21,22] have shown that injection of hemocoagulase into rabbits accelerated blood coagulation without affecting platelet concentration. A study by Nascimento da Costa et al [23] found that hemocoagulase therapy does not confer the risk of deep vein thrombosis in the lower limb and is clinically safe and highly reliable in elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies [19,20] have demonstrated that the application of hemocoagulase during hepatobiliary surgery can effectively reduce intraoperative bleeding volume without affecting the coagulation functions of patients. Furthermore, other studies [21,22] have shown that injection of hemocoagulase into rabbits accelerated blood coagulation without affecting platelet concentration. A study by Nascimento da Costa et al [23] found that hemocoagulase therapy does not confer the risk of deep vein thrombosis in the lower limb and is clinically safe and highly reliable in elderly patients.…”
Section: Discussionmentioning
confidence: 96%